Analisis Manajemen Strategi Bersaing Dengan Matriks Ie, Matriks Swot Dan Matriks Qspm Pada Pt. Xyz. - Evelyn Evelyn (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The purpose of this research is to evaluate, analyze the potential and existing of PT. XYZ. From this research Management, PT. XYZ is expected to be able to choose the proper strategic management action. This research used a descriptive qualitative method. For Business Development Strategy analysis, this study used EFE and IFE matrix, IE matrix, SWOT matrix and QSPM. The study found that PT. XYZ was in a strong position in making use of the power possessed and able to overcome the existing weaknesses the total IFE was 3.57 whose value was classified as exploiting the existing opportunity level. Meanwhile, the value of EFE coping the threat was 3,25.  IE matrix showed that PT XYZ has used growth and build strategies whose alternative strategies can be used to develop its business.